Protective efficacy of a human endogenous retrovirus envelope-coated, nonreplicable, baculovirus-based hemagglutin vaccine against pandemic influenza H1N1 2009. - Jae-Yoo Choi; Yong-Dae Gwon; Jeong-Ki Kim; Yeon-Dong Cho; Yoon-Ki Heo; Han-Sam Cho; Tae-Jin Choi; Ha-Ryoung Poo; Yu-Kyoung Oh; Young Bong Kim (PLoS ONE, 2013)
Despite the advantages of DNA vaccines, overcoming their lower efficacy relative to that of conventional vaccines remains a challenge. Here, we constructed a human endogenous retrovirus (HERV) envelope-coated, nonreplicable, baculovirus-based HA vaccine against swine influenza A/California/04/2009(H1N1) hemagglutin (HA) (AcHERV-sH1N1-HA) as an alternative to conventional vaccines and evaluated its efficacy in two strains of mice, BALB/c and C57BL/6. A commercially available, killed virus vaccine was used as a positive control. Mice were intramuscularly administered AcHERV-sH1N1-HA or the commercial vaccine and subsequently given two booster injections. Compared with the commercial vaccine, AcHERV-sH1N1-HA induced significantly higher levels of cellular immune responses in both BALB/c and C57BL/6 mice. Unlike cellular immune responses, humoral immune responses depended on the strain of mice. Following immunization with AcHERV-sH1N1-HA, C57BL/6 mice showed HA-specific IgG titers 10- to 100-fold lower than those of BALB/c mice. In line with the different levels of humoral immune responses, the survival of immunized mice after intranasal challenge with sH1N1 virus (A/California/04/2009) depended on the strain. After challenge with 10-times the median lethal dose (MLD50) of sH1N1 virus, 100% of BALB/c mice immunized with the commercial vaccine or AcHERV-sH1N1-HA survived. In contrast, C57BL/6 mice immunized with AcHERV-sH1N1-HA or the commercial vaccine showed 60% and 70% survival respectively, after challenge with sH1N1 virus. In all mice, virus titers and results of histological analyses of lung tissues were consistent with the survival data. Our results indicate the importance of humoral immune response as a major defense system against influenza viral infection. Moreover, the complete survival of BALB/c mice immunized with AcHERV-sH1N1-HA after challenge with sH1N1 virus suggests the potential of baculoviral vector-based vaccines to achieve an efficacy comparable to that of killed virus vaccines.